2017
DOI: 10.1111/mec.14396
|View full text |Cite
|
Sign up to set email alerts
|

Distinct microbial communities in the active and permafrost layers on the Tibetan Plateau

Abstract: Permafrost represents an important understudied genetic resource. Soil microorganisms play important roles in regulating biogeochemical cycles and maintaining ecosystem function. However, our knowledge of patterns and drivers of permafrost microbial communities is limited over broad geographic scales. Using high-throughput Illumina sequencing, this study compared soil bacterial, archaeal and fungal communities between the active and permafrost layers on the Tibetan Plateau. Our results indicated that microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 66 publications
12
46
0
Order By: Relevance
“…Our results demonstrated that nitrogen and the C:N ratio explained a greater proportion of the bacterial community structure than TOC. This is consistent with the previous findings that nitrogen availability strongly regulates microbial community structure and function in the permafrost soils of Arctic and Tibetan Plateau (Chen et al, 2018;Chen et al, 2017;Yergeau et al, 2010). Significantly different soil carbon and nitrogen were observed among the various permafrost thawing statuses, but not among the different permafrost ages (Figs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrated that nitrogen and the C:N ratio explained a greater proportion of the bacterial community structure than TOC. This is consistent with the previous findings that nitrogen availability strongly regulates microbial community structure and function in the permafrost soils of Arctic and Tibetan Plateau (Chen et al, 2018;Chen et al, 2017;Yergeau et al, 2010). Significantly different soil carbon and nitrogen were observed among the various permafrost thawing statuses, but not among the different permafrost ages (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…The bacteria richness was significantly higher in the active layer soil (Fig. 2a), and this is consistent with the previous findings that permafrost thawing significantly increases bacterial richness in soil in the Tibetan Plateau and the high Arctic (Chen et al, 2017;Schostag et al, 2019;Wu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Soil microorganisms play an indispensable role in mediating the biogeochemical cycles of nutrient elements, such as C, N, S and P, and in maintaining ecosystem functions and services (Falkowski et al ., 2008; Wagg et al ., 2014; Chen et al ., 2017). Microorganisms in complex soil matrices are generally structured and form complex interconnected microbial networks (Barberán et al ., 2012; Ma et al ., 2016; Shi et al ., 2016; Morriën et al ., 2017; de Vries et al ., 2018; Banerjee et al ., 2019), where microbes interact through multiple processes, including competition, facilitation and inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…They are important components of material cycling and energy flow in the ecosystem. They are widely distributed in various terrestrial environments such as forests [2,3], grasslands [4,5], hot springs [6,7], permafrost [8,9] and marsh wetlands [10,11]. Fungi have different species composition and distribution patterns in diverse habitats, thus forming complex fungal communities [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%